Convergence, divergence and policy: Portugal in the European Union. Issue 5 (29th July 2019) - Lains, Pedro
Abstract: This article deals with the connections between economic policy and economic convergence and divergence in the European Union, by looking at the case of Portugal, still today one of its least developed member states. European and domestic economic policies changed across the period here studied, shifting from an emphasis on programmes aimed at fostering investment in infrastructure and knowledge, such as the structural and regional development funds, to policies giving greater relevance to fiscal and financial equilibria. This shift in policies was followed by economic divergence. As the negative correlation between growth and monetarist policies became increasingly salient, electoral shifts and governmental change led to an overhaul of economic policy. One-size-fits-all European monetary policies lowered the potential for integration, whereas a higher level of domestic participation may lead to the opposite effect, opening up the prospect of higher growth and a return to a slower, but more balanced economic convergence. The experience of the periphery may therefore have lessons for the deepening of European integration.